Endangered multi-cultural heritage in Penang: An evoluation of the laws and policies - Abdullah, N.C. (2008)
﻿The multi-racial society in Penang has brought about the evolution of a multi-cultural historical city, nominated for listing in the World Heritage List. Although the repeal of the Rent Control Act 1966 was among others to address the problem of decaying inner city environment, in 1999, Penang could not escape from being listed by the World Monuments Watch as one of the World's Hundred Most Endangered Sites. This paper explores the laws and policies of the conservation and preservation of cultural heritage in Penang which contributes to this vulnerable phenomenon.